2011
DOI: 10.4067/s0718-58392011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Rates and Split Nitrogen Fertilization on Grain Yield and its Components in Flooded Rice

Abstract: Nutritional management in rice (Oryza sativa L.) crops is mainly associated with N fertilization, which is difficult to adjust in field conditions due to variations in soil type and climatic conditions. Between 28 000 and 46 000 ha per year is dedicated to rice production in Chile and profits depend on fertilization. A field experiment determine the effect of N rates and split N fertilization on grain yield and its components was carried out in two locations during two consecutive seasons (2007 to 2009), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
23
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
10
23
1
1
Order By: Relevance
“…Garin yield in 2 split to 4 split were 7702, 7741 and 7818 kg/ha respectively (Table 3). Split N fertilization there was a significant effect (p<0.05) on the grain yield and the highest values were obtained with (1) 33% n at sowing, 33% at tillering and 34% at panicle initiation and (2) 50% at swing and 50% at panicle initiation (Hirzel et al, 2011). The results showed that the fertilizer treatment had significant effect on Lcc values at different growth stages.…”
Section: Resultsmentioning
confidence: 85%
“…Garin yield in 2 split to 4 split were 7702, 7741 and 7818 kg/ha respectively (Table 3). Split N fertilization there was a significant effect (p<0.05) on the grain yield and the highest values were obtained with (1) 33% n at sowing, 33% at tillering and 34% at panicle initiation and (2) 50% at swing and 50% at panicle initiation (Hirzel et al, 2011). The results showed that the fertilizer treatment had significant effect on Lcc values at different growth stages.…”
Section: Resultsmentioning
confidence: 85%
“…Temperature descriptions for all environments are shown in Figure 1. Soils were classified as Vertisol for Parral and Chillán and Inceptisol for San Carlos (Hirzel et al, 2011). Four experimental lines and six cultivars from the Chilean Rice Breeding Program were studied (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 60 kg P2O5 and 60 kg K2O were applied as triple superphosphate and potassium chloride, respectively. These N rates were chosen because they were verified in previous experiments in the same study area where they produced a range of crop responses (Ortega, 2007;Hirzel et al, 2011a). Each experimental unit was 15 m 2 and all plots were cultivated under traditional agronomic management to optimize crop growth in accordance with standard agronomic practices for rice crops in central Chile.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in agronomic crop management such as weed control, new cultivars, and N fertilization can improve productivity and profitability as well as reduce adverse environmental impacts (Angus et al, 1994;De-Xi et al, 2007;Soon et al, 2007;Hirzel et al, 2011a). Nitrogen is the main nutrient associated with yield, but N management responds differently to rice type (indica or japonica associated with climate requirement and interaction with N nutrition), cultivar, geographic zone, and other crop practices (Angus et al, 1994;Ying et al, 1998;Bouman et al, 2007;De-Xi et al, 2007;Huang et al, 2008;Jing et al, 2008;Hirzel et al, 2011a). Similarly, fertilization management and genotype × environment interaction generate differences in plant nutrient composition (Mengel and Kirkby, 1987); they affect crop extraction, rice plant yield components, and N use efficiency (Ying et al, 1998;Kapoor et al, 2008;Matsunami et al, 2009;Taylaran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation